1990
DOI: 10.1111/j.1468-232x.1990.tb00752.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Capital Theory: Implications for HR Managers

Abstract: This paper reviews some of the contributions of and challenges to human capital theory. It focuses on the alleged link between earings and education and experience and on competing explanations for observed earning differentis by race and by gender. The review concludes that while human capital theory provides some central insights about the supply side of the labor market, the challenges to this theory suggest that the demand side od the market, i.e., the actions of human resource managers, also play a key ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(113 citation statements)
references
References 0 publications
5
107
0
1
Order By: Relevance
“…Human capital theory suggests that there is a correlation between human capital and organizational performance, which can benefit from the accumulation of firm-specific, valuable human capital (Danes et al, 2009;Strober, 1990). According to the resource-based view, human capital is the most valuable and difficult type of resource to imitate because it is, to a large degree, the product of complex social structures that have been built over time (Barney, 1991).…”
Section: Development Of Human Capital Theorymentioning
confidence: 98%
“…Human capital theory suggests that there is a correlation between human capital and organizational performance, which can benefit from the accumulation of firm-specific, valuable human capital (Danes et al, 2009;Strober, 1990). According to the resource-based view, human capital is the most valuable and difficult type of resource to imitate because it is, to a large degree, the product of complex social structures that have been built over time (Barney, 1991).…”
Section: Development Of Human Capital Theorymentioning
confidence: 98%
“…The first demographic variable was the age of the CEO (AGE). A number of studies have documented the importance of CEO age in determining compensation (Strober, 1990) as well as how the CEO manages the firm. Lucier, Schuyt, and Spiegel (2003) found that individuals average 50 years of age when promoted to the CEO position.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Rather, we seek to alert scholars and practitioners of higher education of a possible alternative way of viewing the determination of faculty salaries. Just as signaling theorists and institutional theorists in the 1970s led labor economists to understand that the human capital theory is only one possible explanation for the correlation between earnings and educational attainment, and that the causal mechanism for the correlation may include numerous other factors (See Strober, 1990, for a review of these arguments), our work aims to provide a recognition that faculty salaries are not solely determined by human capital and ''productivity.'' Of equal importance, our paper seeks to show that viewing faculty salaries as returns to the generation of prestige provides an opening for serious discussion about the missions of higher education.…”
mentioning
confidence: 98%